2021
DOI: 10.15695/jstem/v4i2.07
|View full text |Cite
|
Sign up to set email alerts
|

Explorers Virtual Internship: Fostering Rightful Presence and Sense of Belonging in an Online High School Internship Program

Abstract: This paper describes the "Explorers Virtual Internship" (EVI), which was designed and presented in the 2020-21 school year by the Fred Hutchinson Cancer Research Center. Despite our initial wariness about creating a virtual internship, the shift helped us make valuable innovations to our programming. EVI paired 11 high school interns with mentors to work on individual research projects. We designed our program to foster a sense of belonging and "rightful presence" in biomedical research among the interns, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…However, the participants also experienced insufficient experiential learning and application of theoretical knowledge during the virtual pharmacy internship because they could not do the activities on-site physically. This is evidently significant, as Lalish et al (2021) stated that the students found the online setting convenient, but they missed acquiring skills in a hands-on situation [29]. According to Hora et al (2021), interns who participate in virtual internships may miss out on learning essential "soft skills" because they are not physically or socially connected in a professional setting [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, the participants also experienced insufficient experiential learning and application of theoretical knowledge during the virtual pharmacy internship because they could not do the activities on-site physically. This is evidently significant, as Lalish et al (2021) stated that the students found the online setting convenient, but they missed acquiring skills in a hands-on situation [29]. According to Hora et al (2021), interns who participate in virtual internships may miss out on learning essential "soft skills" because they are not physically or socially connected in a professional setting [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the Explorers program was a 2-week in-person summer outreach program aimed at rising 10th to 11th graders from underrepresented backgrounds in STEM. 23 In-person program in the summer of 2020 was not available and instead the program held a scaled-down virtual program (Virtual Explorations in Cancer Research [VECR]) that met for 3 hours per week for 6 weeks. 23 The COVID-19 pandemic restrictions were causing major disruptions to the lives of high schoolers, especially those from marginalized communities, it was found that students were more eager to stay connected and make new connections with scientists and like-minded students.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In-person program in the summer of 2020 was not available and instead the program held a scaled-down virtual program (Virtual Explorations in Cancer Research [VECR]) that met for 3 hours per week for 6 weeks. 23 The COVID-19 pandemic restrictions were causing major disruptions to the lives of high schoolers, especially those from marginalized communities, it was found that students were more eager to stay connected and make new connections with scientists and like-minded students. 23 Personal connections and research experiences were more valuable, thus, instead of reducing programming in response to the pandemic, there was a need to create more opportunities for student engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest the potential of exploring more "indirect routes" to enhancing contribution to knowledge building in science classrooms that others have tested by focusing on improving students' sense of belonging. This approach could entail the teacher spending time developing relationships with students and among students, as well as giving opportunities for students to learn about one another's goals for learning (Lalish et al, 2021). This kind of strategy has been tested in undergraduate biology and physics classrooms, where it was particularly impactful for racially minoritized students and women in those classes (Binning et al, 2020).…”
Section: Limitations Of the Studymentioning
confidence: 99%